“Utilización de harina de frijol de palo (Cajanus Cajan) En la elaboración de manjar blanco” - Perea Pinedo, Julio César (2007)
The present investigation work, had for purpose to increment de blancmang's proteic contents utilizing wooden-bean flour (Cajanus cajan) and this way impulsing production and this one use leguminous. Previously to the delicacy elaboration carne true tha analyses correspondent proximales that went in order to the wooden bean: 19.12%, 1.49%, 3.78%, 1021%, 7.82% of protein, fat, ash, humidity and fiber, respectively, and went in order to the milk: 2.95%, 3.70%, 87.50%, 1.80%, 6.7 y 1.030 Kg/m 3 of protein, fat, humidity, acidity, pH and density respectively. The flour's elaboration had following sequence: wooden-bean -+ weighed -+ cleanliness and selection -+ scalded -+ dried -+ willing -+ sieved -+ wooden-bean flour, and the 68% performance was obtained. After the delicacy in his distinct formulations was come from to the elaboration, and if was the process's sequence: Fresh milk -+ pasteurization -+ concentration -+ cooled -+ envasad -+ stored -+ blancmange; that they were subdved to an organoleptica evaluation, having greater acceptance four half way trained judges's group, the F6 formulation, that was containing: sugar 30% and flour 24%; posteriorly the mass balance was complished stop determining the performance, it was obtained: 45.85%. The composition the delicacy's proximal went: 34.38%, 11.18%, 2. 72%, 1.64% and 0.21 % of humidity, protein, fat, ahs and acidity, respectively, posteriorly biological evaluations came true , it wa obtained the net protein utilization (NPU) of 55.81%, the proteic efficiency relation (PER) of 1. 74, digestibilidad of 68.97% and the biological value (VB) of 79.07%, the microbiological controls were numeration of Aerobic germ misfiles(9. 7x103 , 19. 5x 103 y 32. 8x103 ) and moulds and yeasts numbering(86, 10 y 125) ; finally the amino acids computation carne true a proteic score was obtained of 54.99%.